Relación entre la inserción laboral femenina y el crecimiento económico de Ecuador, periodo 1985-2020, mediante un modelo econométrico de series de tiempo. - Ortiz Padilla, Cristopher Emanuel (2024)
In Ecuador, low female labor participation is a socioeconomic problem that has blocked labor market development and long-term economic growth. Although, global female participation rate is 53.9%, women's labor insertion is below the national average and hardly varies annually. In contrast, male participation exceeds 77%, which means that there are fewer women looking for employment compared to men. The research focuses on the relationship between female labor insertion and economic growth in Ecuador between 1985 and 2020. The data was collected from the National Institute of Statistics and Censuses (INEC, acronyms in Spanish) (2021), Central Bank of Ecuador (2021), World Bank (2021) and Global Footprint Network (2021); and also, descriptive and econometric techniques were used. The results show that female labor participation has a positive impact on economic growth in the short and long term, establishing a unidirectional causal relationship towards the Gross Domestic Product. As a result, it is suggested to implement policies that offer tax benefits to companies that hire low- income women or those who have been unemployed for a long time. Furthermore, it is crucial to develop training programs to improve women's skills and expand their access to worth jobs.